MANAJAMEN STRATEGIS MENGATASI GALAT PENERIMA KUR DI KABUPATEN LOMBOK TIMUR - LALU MUH. KABUL (Universitas Mahasaraswati Mataram, 2018)
This research describes strategical management to overcome error beneficiaries of credit for people business (KUR). The research method used was qualitative. Data sources were primary and secondary data. For data collecting used interview and FGD. The research result showed that error beneficiaries of KUR consisted of exclusion error and inclusion error. Strategy that used to overcome exculison error includes extensification and intensification. Meanwhile, socialization is a strategy that used to overcome inclusionerror.